Seesaw limit of the Nelson-Barr mechanism - A.L. Cherchiglia; A.G. Dias; J. Leite; C.C. Nishi (Physics Letters B)
We investigate how the solution to the strong CP problem and the explanation for the observed fermion mass hierarchies can be intrinsically related. Specifically, we explore the Nelson-Barr mechanism and identify its “seesaw limit”, where light quark masses are suppressed by large CP-violating terms. Upon adding three (two) vector-like quarks that mix with the down-type (up-type) quark sector of the Standard Model, we demonstrate how the lack of CP violation in the strong sector and the observed quark mass hierarchy can be simultaneously achieved.